Amelia Jane is naughty again - Blyton, Enid. (b)
New editions, with new illustrations and new format, of all four Amelia Jane titles. Amelia Jane is big, bad and the terror of the toy cupboard! In this book, Amelia Jane plays all sorts of tricks on the toys. She steals the teddy bear's necklace, causes chaos with a boomerang. Can the toys teach her a lesson?
Keywords: Amelia Jane -- Juvenile fiction. -- (Fictitious character); Children's stories; Amelia Jane -- (Fictitious character).